Expression of epithelial calcium transport system in rat cochlea and vestibular labyrinth - Yamauchi, D.; Nakaya, K.; Raveendran, N. N.; Harbidge, D. G.; Singh, R.; Wangemann, Antje Philine; Marcus, Daniel C. (My University, 2017)
Background: The low luminal Ca2+ concentration of mammalian endolymph in the inner ear is required for normal hearing and balance. We recently reported the expression of mRNA for a Ca2+-absorptive transport system in primary cultures of semicircular canal duct (SCCD) epithelium. Results: We now identify this system in native vestibular and cochlear tissues by qRT-PCR, immunoblots and confocal immunolocalization. Transcripts were found and quantified for several isoforms of epithelial calcium channels (TRPV5, TRPV6), calcium buffer proteins (calbindin-D9K, calbindin-D28K), sodium-calcium exchangers (NCX1, NCX2, NCX3) and plasma membrane Ca2+-ATPase (PMCA1, PMCA2, PMCA3, and PMCA4) in native SCCD, cochlear lateral wall (LW) and stria vascularis (SV) of adult rat as well as Ca2+ channels in neonatal SCCD. All components were expressed except TRPV6 in SV and PMCA2 in SCCD. 1,25-(OH)2vitamin D3 (VitD) significantly up-regulated transcripts of TRPV5 in SCCD, calbindin-D9K in SCCD and LW, NCX2 in LW, while PMCA4 in SCCD and PMCA3 in LW were down-regulated. The expression of TRPV5 relative to TRPV6 was in the sequence SV > Neonatal SCCD > Adult SCCD > LW > primary culture SCCD. Expression of TRPV5 protein from primary culture of SCCD did not increase significantly when cells were incubated with VitD (1.2 times control. P > 0.05). Immunolocalization showed the distribution of TRPV5 and TRPV6. TRPV5 was found near the apical membrane of strial marginal cells and both TRPV5 and TRPV6 in outer and inner sulcus cells of the cochlea and in the SCCD of the vestibular system. Conclusions: These findings demonstrate for the first time the expression of a complete Ca2+ absorptive system in native cochlear and vestibular tissues. Regulation by vitamin D remains equivocal since the results support the regulation of this system at the transcript level but evidence for control of the TRPV5 channel protein was lacking.
Citation: Yamauchi, D., Nakaya, K., Raveendran, N. N., Harbidge, D. G., Singh, R., Wangemann, P., & Marcus, D. C. (2010). Expression of epithelial calcium transport system in rat cochlea and vestibular labyrinth. BMC Physiol, 10. doi:10.1186/1472-6793-10-1